Impact of Fixed Orthodontic Appliance Treatment on Children’s Mental Health, Quality of Life and Social Context: A Scoping Review - Schmahl T; Steinhäuser J; Wewetzer L; Goetz K (Patient Preference and Adherence)
Teresa Schmahl, Jost Steinhäuser, Larisa Wewetzer, Katja Goetz Institute of Family Medicine, University Medical Centre Schleswig-Holstein, Luebeck, GermanyCorrespondence: Teresa Schmahl, Institute of Family Medicine, University Medical Centre Schleswig-Holstein, Campus Luebeck, Maria-Goeppert-Straße 9a, Luebeck, 23538, Germany, Tel +49 451 3101-8042, Email Teresa.Schmahl@uni-luebeck.dePurpose: There has been a consistent upward trend in orthodontic treatment across all age groups. It is one of the longest and most common medical interventions for children. There is a growing interest in the connection between orthodontic treatment and children’s oral health-related quality of life to provide an insight into treatment needs and outcomes, as well as long-term improvement in oral health. However, to our knowledge the impact of fixed orthodontic appliances on the mental health of the children, their social context and their families have not been sufficiently investigated and have not yet been summarized. The objectives were to provide an overview of empirical research regarding the impact of fixed orthodontic appliances on children’s mental health, social context and families.Patients and Methods: A comprehensive literature search was conducted across four databases. Studies investigating the effects and impact of fixed appliances on mental health, social context and families of children up to the age of 18 were included. Data were extracted by two independent reviewers. The studies were reviewed, their results compared and analyzed narratively.Results: Ultimately, 30 studies were analyzed. The most common conclusions were that oral health-related quality of life worsens during and improves again after treatment. The extent to which orthodontic treatment limits or affects children’s lives, their mental health, personality, personal development and behavior has not been extensively investigated.Conclusion: Evidence of the impact of fixed orthodontic appliances on mental health and social context of children and their families is basically missing. However, this would be crucial for the consideration of evidence-based recommendations. Therefore, the impact of fixed orthodontic appliances should be addressed in further empirical studies.Keywords: fixed orthodontic appliances, children, mental health, social context, orthodontics, oral health-related quality of life, scoping review